2021
DOI: 10.1002/adom.202101673
|View full text |Cite
|
Sign up to set email alerts
|

Direction Controllable Nano‐Patterning of Titanium by Ultrafast Laser for Surface Coloring and Optical Encryption

Abstract: Different applications of TiO 2 metasurfaces, such as dynamic metadevices, [8] metalens, [10] color nanoprinting, [2,[11][12][13] vacuum ultraviolet third harmonic generation, [14] and holo graphy [15,16] have been demonstrated. The fabrication of delicate TiO 2 nanostructures is the basis for the applications of TiO 2 metasurfaces.Laser processing is a maskless and path-directed technique, and it has been used in cutting, welding, drilling, and surface coloring. [17][18][19][20][21][22] However, the resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…To date, direct patterning by an ultrafast laser has been demonstrated to be an effective technique for spatiotemporally micromachining and engineering materials. As a noncontact method, an ultrafast laser can directly ablate object materials and increase photothermal energy in local areas, thereby inducing chemical reactions in local positions. Qiu and Dong reported that a femtosecond laser (fs) laser could inject energy with an ultrashort amount of time, which leads to strong thermal accumulation and thereby increases the local pressure and temperature (>2500 °C) above the liquidus of glass composition, so that the crystallization of perovskite nanoparticles (NPs) inside the glassy matrix is realized. , Zhizhchenko et al produced donut-shaped MAPbI 3 whispering-gallery mode microlasers by utilizing the fs laser to remove selective regions of MAPbI 3 films via thermal ablation . The reported ultrafast laser-patterned microstructures mainly rely on thermal ablation by direct laser energy deposition; however, the undesirable crystallizations and cracks in the adjacently focused areas are inevitable, limiting the resolution of the patterned perovskite.…”
Section: Description Of Cw Laser Patterning Methodsmentioning
confidence: 99%
“…To date, direct patterning by an ultrafast laser has been demonstrated to be an effective technique for spatiotemporally micromachining and engineering materials. As a noncontact method, an ultrafast laser can directly ablate object materials and increase photothermal energy in local areas, thereby inducing chemical reactions in local positions. Qiu and Dong reported that a femtosecond laser (fs) laser could inject energy with an ultrashort amount of time, which leads to strong thermal accumulation and thereby increases the local pressure and temperature (>2500 °C) above the liquidus of glass composition, so that the crystallization of perovskite nanoparticles (NPs) inside the glassy matrix is realized. , Zhizhchenko et al produced donut-shaped MAPbI 3 whispering-gallery mode microlasers by utilizing the fs laser to remove selective regions of MAPbI 3 films via thermal ablation . The reported ultrafast laser-patterned microstructures mainly rely on thermal ablation by direct laser energy deposition; however, the undesirable crystallizations and cracks in the adjacently focused areas are inevitable, limiting the resolution of the patterned perovskite.…”
Section: Description Of Cw Laser Patterning Methodsmentioning
confidence: 99%
“…It greatly enriches its utilization in both industry and research fields. Nowadays, structural colors have become a prominent choice in wide applications, such as visual aesthetic display, anti-counterfeiting, and multiplexed optical storage. ,, …”
Section: Introductionmentioning
confidence: 99%
“…However, this method can only be arranged regularly along the substrate surface, which is a challenge for the arbitrary design and composite patterns. , Nanoimprinting is also a mass-productive and high-resolution method, but it is difficult to become a general method as a result of the limitation of imprinting on flexible materials, such as polymers. Otherwise, it is susceptible to be damaged during the transfer process. ,, Although focused electron or ion beam lithography enables the preparation of complex, high-precision structures, the fabrication is often confined within a very small scale as a result of the limitations of complicated procedures and high cost, leading to the structural color observation usually with the help of a microscope. , In contrast to the aforementioned situations, the recent years of ultrafast laser manufacturing development strongly demonstrates its unique advantages in the structural color fabrication, showing a flexible, one-step, and contactless procedure and remarkably suitability for a wide scope of materials. , The direct laser writing process is a prominent fabrication method, producing nanostructures that are often featured with high resolution, , and suitable for integration applications, such as optical storage. However, although a tight focus of the laser beam can act as a “pensile” to have a micro- or nanoscale fabrication in a mask-free and flexible way, the point-by-point processing still makes it confined, especially in work efficiency. , The spatial light modulator (SLM) has been used by many research groups for ultrafast laser manufacturing with more efficiency. , However, during such SLM-assisted laser processing, a tight focus of the laser beam spot was often demonstrated, which still limits its capability for further improvements.…”
Section: Introductionmentioning
confidence: 99%
“…The femtosecond laser processing does not need a vacuum environment. It could achieve nanoscale processing precision and has been widely used in the nanofabrication field. , This technology has been used to fabricate supercapacitors in some previous works. Li et al used a femtosecond laser to cut MXene electrodes with a double-sided configuration.…”
Section: Introductionmentioning
confidence: 99%